Distal end force sensing with optical fiber Bragg gratings for tendon-sheath mechanisms in flexible endoscopic robots - Lai, Wenjie (2020)
Accurate haptic feedback is a critical challenge for surgical robots, especially for flexible endoscopic surgical robots whose transmission systems are Tendon-Sheath Mechanisms (TSMs) with highly nonlinear friction profiles and force hysteresis. For distal end haptic sensing of TSMs, this paper, for the first time, proposes to measure the compression force on the sheath at the distal end so that the tension force on the tendon, which equals the compression force on the sheath, can be obtained. A new force sensor, i.e., a nitinol tube attached with an optical Fiber Bragg Grating (FBG) fiber, is proposed to measure the compression force on the sheath. This sensor, with similar diameter and configuration (hollow) as the sheath, can be compactly integrated with TSMs and surgical end-effectors. In this paper, mechanics analysis and verification tests are presented to reveal the relationship between the tension force on the tendon and the compression force on the sheath. The proposed force sensor was calibrated in tests with a sensitivity of 24.28 pm/N and integrated with a tendon-sheath driven grasper to demonstrate the effectiveness of the proposed approach and sensor. The proposed approach and sensor can also be applied for a variety of TSMs-driven systems, such as robotic fingers/hands, wearable devices, and rehabilitation devices.